Effect of schleichera oleosa bark extract in wound healing activity - PATHAK, RISHITA; JAIN, DR. SOURABH; BUNDELA, RAGINI; SHUKLA, DR. KARUNAKAR; JAIN, NEHA (International Journal of Multidisciplinary Research and Studies, 2023)
This study evaluates the wound healing potential of Schleichera oleosa bark extract using an excision wound model in albino rats. The plant material was collected, authenticated, and extracted using methanol via Soxhlet apparatus. Pharmacognostic, physicochemical, and phytochemical analyses revealed the presence of key bioactive constituents such as flavonoids, tannins, terpenoids, and saponins. Two concentrations (5% and 10%) of the extract were formulated into ointments using standard British Pharmacopoeia guidelines. These ointments were applied to wounds in rats and compared with a control group and a standard povidone-iodine treated group. The results showed a significant, dose-dependent increase in wound contraction, particularly in the 10% extract group, which exhibited nearly complete healing by day 22. Statistical analysis confirmed the extract's efficacy with p-values <0.05 and <0.0001 on the 7th and 14th days, respectively. The enhanced wound healing is attributed to the extract’s antioxidant, anti-inflammatory, and antimicrobial properties. The study supports the traditional use of S. oleosa in wound management and underscores its therapeutic potential as a natural alternative for wound care.